1992
DOI: 10.1017/s0031182000073662
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of canine leishmaniasis: prevalence, incidence and basic reproduction number calculated from a cross-sectional serological survey on the island of Gozo, Malta

Abstract: Assessment of the resilience of canine leishmaniasis to control or, more ambitiously, the effort needed to eradicate infection, requires an estimate of the basic case reproduction number (R0). This paper applies the theoretical results of Hasibeder, Dye & Carpenter (1992) to data from a cross-sectional survey on the Maltese island of Gozo in which dogs of known age, sex and occupation (pet, guard etc) were subjected to three different serological tests for the presence of specific antibody (IFAT, DAT and ELISA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
0
4

Year Published

1993
1993
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 12 publications
3
58
0
4
Order By: Relevance
“…We have recently attempted to obtain all three from data collected during a cross-sectional survey of canine leishmaniasis in the Maltese islands [1,2]. The greatest obstacle to doing so was the interpretation of serological data.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have recently attempted to obtain all three from data collected during a cross-sectional survey of canine leishmaniasis in the Maltese islands [1,2]. The greatest obstacle to doing so was the interpretation of serological data.…”
Section: Introductionmentioning
confidence: 99%
“…The distinction is underlined by the fact that antibody titres obtained from populations of known positives and non-endemic controls are often bimodally distributed [e.g. 11], whereas titre distributions obtained from natural populations in which disease is endemic are commonly unimodal [1,4,8,12]. Where bimodal distributions of titres are found in field samples, the peaks corresponding to positives and negatives are never completely separated [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have been demonstrated the limitations to identify asymptomatic dogs using the available tests (DYE et al, 1992;REITHINGER et al, 2002;RHALEM et al, 1999). Porrozzi et al (2007) showed that ELISA based on crude antigens shown minor percentage (30%) for asymptomatic dogs than that ELISA based on recombinant leishmanial antigens rA2 (88%); rK39 and rK26 (66%).…”
Section: Discussionmentioning
confidence: 99%
“…Refinamientos mensuales de los datos de incidencias ayudarían a refinamientos de las estimaciones de R o . Es importante destacar que estas estimaciones se realizaron bajo las hipótesis de homogeneidad de las poblaciones de los hospedadores, hipótesis de poblaciones heterogéneas proporcionarían mayores estimaciones como en los trabajos de Dye et al 12 y de Hasibeder et al 5 .…”
Section: Discussionunclassified